Development of an Orthosis to Compensate Volumetric Dysmetria of Feet - Magalhães, António; Peixoto, Carla (Journal of Science and Technology, 2024)
The concept of symmetry applied to the two halves of the human body has been the subject of reflection by anatomists. One of the most common inequalities is dysmetry of the lower limbs (LL), especially the legs and/or feet. In the case of a height difference in the legs, if it is very pronounced, it is necessary to develop strategies capable of correcting or reducing its impact on the quality of life of people who live with it daily. A rare type of dysmetria is the volumetric difference of the feet, not accompanied by changes in the length of the legs. In these cases, filling with conventional orthopedic insoles to improve the fixation of the foot inside the shoe is completely inappropriate because it slightly increases the length of the respective lower limb, which is reflected in changes in the spine that can degenerate into severe scoliosis. To solve these problems, a volumetric compensation orthosis applicable to this type of situation was developed. Using modern three-dimensional scanning and 3D printing techniques, an orthosis was customized for placement inside the shoes of an individual with this volumetric anomaly. To ensure walking comfort, a common flexible material (TPU) was chosen, and the printing parameters were studied based on feedback given by the user. As a measure of the effectiveness of the developed product and to analyze the effect produced, tests were carried out to compare gait patterns before and after the correction was established. The results found showed an approximation to standard gait patterns, a considerable improvement in the fixation of the foot inside the shoe and an interchangeability that allows the use of the orthosis in any type of footwear, such as classic shoes, boots or sneakers.